Manuel Balado and the cranial and spinal pressure differences.: https://doi.org/10.59156/revista.v37i02.536 - Picard, Nelson; Furst, Jorge E; Zanardi, Carlos A.; Gruarín, Juan F J (Revista Argentina de Neurocirugía, 2023)
Manuel Balado (1897-1942), a pioneer of Argentinian neurosurgery, is best known for his studies on the optic pathway and iodoventriculography. Their concerns, however, encompassed numerous other fields, one of them being the pressure differences between the cranial and spinal compartments. In his Lessons on Neurological Surgery, the first exclusive text of the specialty in Argentina, he made an original description of them. We reproduce here several of his schemes, most of them still valid, and we analyze them in their context and in the light of current knowledge. We did not find similar descriptions in the bibliography of his time.